The functional role of Nudt2 in human triple negative breast cancer - Abu-Rahmah, Rasha; Nechushtan, Hovav; Hidmi, Sanaa; Meirovitz, Amichay; Razin, Ehud; Peretz, Tamar (Frontiers in Oncology, 2024)
The main known function of Nudix hydrolase 2 (Nudt2) is to hydrolyze the secondary messenger diadenosine 5’, 5’’’-p1, p4-tetraphosphate (Ap4A). In this study we examined the role of Nudt2 in breast carcinoma through its expression in human invasive ductal carcinoma tissues, and its functions in human triple negative breast cancer (TNBC) cell lines. A significantly higher expression of Nudt2 was observed in human invasive ductal carcinoma tissues compared to that in normal breast tissue. Knockdown of Nudt2 in TNBC cell lines resulted in a significant reduction in cellular proliferation via the Ki67 marker, accompanied by G0/G1 phase cell cycle arrest, in the migration and invasion of these cells and in tumorigenicity and anchorage-independent growth. It can therefore be concluded that Nudt2 plays a significant role in promoting TNBC growth.